The flame retardant DE-71 (a mixture of polybrominated diphenyl ethers) inhibits human differentiated thyroid cell function in vitro - Kronborg, Thit Mynster (PLoS One, 2017)
BACKGROUND: Normal thyroid function is essential for general growth and metabolism, but can be affected by endocrine disrupting chemicals (EDCs). Polybrominated diphenyl ethers (PBDEs) have been used worldwide to reduce flammability in different materials and are suspected to be EDCs. The production of the commercial Penta- and OctaBDE mixtures is banned, but DecaBDEs and existing products may leak PBDEs into the environment. Our aim was to investigate the effect of the PentaBDE mixture DE-71 on human thyroid cells in vitro. MATERIALS AND METHODS: Primary human thyroid cells were obtained as paraadenomatous tissue and cultured in monolayers. The influence of DE-71 on cyclic adenosine monophosphate (cAMP) and thyroglobulin (Tg) production was examined in the culture medium by competitive radioimmunoassay and enzyme-linked immunosorbent assay, respectively. Real-time quantitative PCR analysis of thyroid-specific genes was performed on the exposed cell cultures. PBDE concentrations were determined in cellular and supernatant fractions of the cultures. RESULTS: DE-71 inhibited Tg-release from TSH-stimulated thyrocytes. At 50 mg/L DE-71, mean Tg production was reduced by 71.9% (range: 8.5–98.7%), and cAMP by 95.1% (range: 91.5–98.8%) compared to controls). Expression of mRNA encoding Tg, TPO and TSHr were significantly inhibited (p<0.0001, p = 0.0079, and p = 0.0002, respectively). The majority of DE-71 added was found in the cell fraction. No cytotoxicity was found. CONCLUSIONS: DE-71 inhibited differentiated thyroid cell functions in a two phase response manner and a concentration-dependent inhibition of Tg and cAMP production, respectively, as well as expression of mRNA encoding Tg, TPO and TSHr. Our findings suggest an inhibiting effect of PBDEs on thyroid cells.